Quaternary Ammonium Based Compound Improves Interfacial Bond and Hydrophobicity of Coirpith-Cement Composite - John Loraña (Camarines Sur Polytechnic Colleges, 2022)
Coir pith is a coconut waste derived from the extraction of coconut fiber that accounts for 70% of total husk. With an estimated 6.7 million husks produced in the Philippines annually, a large fraction of waste known as coir pith is left to rot, thrown or burned. Coir pith in cement board composite is applicable as insulation and a light indoor construction material due to its high-water absorption properties and less strength. The study sought to solve the high-water absorption problem while aiming at improving the strength and durability of the composite that will meet the needs for indoor and outdoor construction materials. According to the study's findings, QUAC increases the hydrophobicity of coir pith-cement composites, improves interfacial bonds, and has the potential for light indoor and outdoor construction.